Musica e Identidad - Oramas Oliva, Óscar (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The article analyzes music as a powerful identification factor throughout the process of formation of the Cuban national identity. Music is one of the most socialized artistic aspects in Cuba. To talk about the causes of the influence of music on the social psychology and identity of the Cuban, it is essential to consider the factors that shaped the nationality: the colonizers and the natives of Africa. National thinkers such as Don Fernando Ortiz, Alejo Carpentier and Rogelio Martínez Furé have explained that African slaves, who contributed so much to the formation of Cuban nationality, and therefore to all Cuban artistic manifestations, through musical instruments and the dances, fought to preserve their respective identities against the Spanish colonialist. It is evident that music played a very important role in the lives of those men, who in good or bad spirits, populated our country. Later music was important in the churches. La Guantanamera, the cha-cha-cha and, finally, the Buenavista Social Club group, are considered urbi e orbi as current testimonies of the Cuban identity. So, Cuban music is a true synthesis of essential elements of its history: colonization, slavery, transculturation and the protest of the oppressed, who channeled their rebellion through expressing their feelings with musical compositions in a spontaneous and later more elaborate way. Music in Cuba has been, and is, an instrument of communication and creation that has shaped the Cuban and constitutes an outstanding ingredient in the formation of cultural and national identity.